2016
DOI: 10.1051/matecconf/20164702009
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Shapes and Sizes on Torsion Behaviour of I-Beam with Web Opening

Abstract: Abstract. Numerical study on torsion behaviour of I-beam with web opening was carried out and presented in this paper. Optimum shapes and sizes which enhance the torsion behaviour of the I-beam with web opening as well as lead to economic design in terms of both manufacture and usage.Comparison is made between I-beam without web opening and I-beam with various shapes and sizes of web opening. Different types of finite elements model, sizes and types of web opening were used to investigate the effect of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Many design guidelines for cold-formed steel members have been established (British Standard BS5950-5, 1998;EN1993-1-1, 2005. Substantial research about section with opening has been performed over many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many design guidelines for cold-formed steel members have been established (British Standard BS5950-5, 1998;EN1993-1-1, 2005. Substantial research about section with opening has been performed over many years.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, it was concluded that the optimum opening size was 0.5 D compared with 0.6 and 0.7 D (De’nan and Hashim, 2016). Section with C-hexagon openings showed lower torsional angles when compared to hexagon, octagon, circular and square openings.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the optimize web sizes, layout and shapes of opening have been found by other researchers to know the stress distribution pattern in the surrounding of the web opening (De'nan and Hashim, 2016). Besides that, the web opening can also be applied for the cross-passing of utility system in the floors (Siddh and Pachpor, 2011).…”
Section: Introductionmentioning
confidence: 99%